1995
DOI: 10.1007/s001250050279
|View full text |Cite
|
Sign up to set email alerts
|

In situ binding of islet hormones in the isolated perfused rat pancreas: evidence for local high concentrations of islet hormones via the islet-acinar axis

Abstract: SummaryInsulin and somatostatin reportedly affect pancreatic acinar cell function via specific receptor binding. Theoretically peri-insular levels depend on the islet-acinar portal system, but the actual hormone levels have never been demonstrated. Rat pancreata were perfused anterogradely or retrogradely with 125I-insulin, -somatostatin, or -glucagon (each, --~ 10-11 mol/1). Tracer binding was determined from differences between influx and efflux radioactivity. Saturable binding was observed for insulin and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…4 At high concentrations, interstitial insulin nourishes exocrine pancreatic cells. 5,6 When pancreatic cancer occurs, insulin may stimulate the growth of the cancer cells as well. In vitro, insulin has been found to stimulate proliferation and glycolysis in pancreatic cancer cells.…”
Section: Intratumoral Hypoxia and Paracrine Insulin Stimulate The Expmentioning
confidence: 99%
“…4 At high concentrations, interstitial insulin nourishes exocrine pancreatic cells. 5,6 When pancreatic cancer occurs, insulin may stimulate the growth of the cancer cells as well. In vitro, insulin has been found to stimulate proliferation and glycolysis in pancreatic cancer cells.…”
Section: Intratumoral Hypoxia and Paracrine Insulin Stimulate The Expmentioning
confidence: 99%
“…Two estimates indicate that the concentration of insulin and somatostatin is in the nanomolar range. The first comes from a study evaluating saturable binding of iodinated tracer for insulin and somatostatin in the rat pancreas perfused anterograde or retrograde (219). Binding was higher for retrograde perfusion which was attributed to endogenous hormone released during anterograde perfusion.…”
Section: B Isletacinar Portal Systemmentioning
confidence: 99%
“…These investigators concluded that the inhibitory effect of insulin antisera was mediated by the local release of and action on the exocrine pancreas of somatostatin and PP (165). In a related study, Nakagawa et al concluded that the net effect of islet peptides on the exocrine pancreas was negative because exocrine secretion was greater with retrograde than anterograde perfusion (219). Thus the action of insulin could be mediated at least in part by suppressing the secretion of inhibitory islet peptides.…”
Section: Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, islet hormone (insulin and somatostatin) receptors exist on the plasma membrane of pancreatic acinar cells and the periacinal islet hormone concentrations are at least 20-fold higher in concentration than those in the systemic circulation . Thus, pancreatic islet hormones may regulate the secretion of the exocrine pancreas (Nakagawa et al, 1995;Hasegawa et al, 1993).…”
Section: Effect Of Islet Hormones On Exocrine Pancreasmentioning
confidence: 99%